Study on characteristic of sediment and bed load transport in sungai Jemberau at Tasik Chini - Siti Noor Marhidayu, Mohamad Sukri (2018)
This study conducted in Sungai Jemberau at Tasik Chini. The objectives of this research was to identify the sediment characteristic and bed load transport in Sungai Jemberau. The bed load transport are analyzed using predicted by DuBoys and Schoklitsch equation, and measured method by Helley-Smith Sampler. Thus, these two methods was compare to obtain the best prediction of bed load transport in Sungai Jemberau. As to identify the sediment characteristics which are particle size and density, the Sieve Analysis and Particle Density Analysis were carried out in the Geotechnical Laboratory, UMP. The classification of sediment from sieving test results was classified using Udden-Wentworth Scale. Analysis for particle size distribution shown the highest median grain size (d_50) was 4.30mm for Sample 3 on 5th March 2017 (Rainy) followed by 3.80mm for Sample 2 on 1st December 2016 (Sunny), 3.20mm for Sample 5 on 12th November 2017 (Rainy) and Sample 6 on 30th January 2018 (Rainy), 2.70mm for Sample 1 on 24th September 2016 (Sunny) and lastly 1.20mm for Sample 4 on 17th May 2017 (Rainy). Mostly, the sediment samples was classified as gravel type. Meanwhile, the density of sediment in Sungai Jemberau were range from 2.34g/cm3 to 2.97g/cm3. These particle size and density of sediment were influence the sediment transport in Sungai Jemberau. Extensive uncontrolled mining activities nearby the Sungai Jemberau were lead to erosion process to occur. In result, it increase the sediment flows into Sungai Jemberau and it becomes worsen during storm or rainfall event. High amount of sediment will settle down in stream bed and make the depth of river become shallow if the sedimentation occurred. At once, the area will face flooding because the river become overflow due to sedimentation process. Then, using DuBoys and Shoklitsch equation, the bed load transport in Sungai Jemberau can be predicted. From the comparison of predicted and measured bed load transport result, DuBoys were selected as the best prediction of bed load transport in Sungai Jemberau because the bed load transport predicted by DuBoys equation were more closest to measured bed transport using Helley-Smith Sampler compared to bed load transport predicted by Schoklitsch equation. However, shown that the predicted bed load transport using DuBoys and Schoklitsch equation were over-estimate because the both equations was develop from abroad and not really suitable to use in river at Malaysia.